2003
DOI: 10.1111/j.1365-2621.2003.tb09629.x
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin Removal from Pistachio Nuts by Natural Natrolite

Abstract: Natrolite was used to explore a physical and safe method to decontaminate aflatoxin-containing pistachio lots. Pistachio nuts with low, medium, and high levels of aflatoxin were subjected to a washing process with a slurry of 5% natrolite. Using thin-layer chromatography and scanning, the aflatoxin contents of the samples were measured. Aflatoxins B 1 and B 2 were found in pistachio nuts. The majority of total aflatoxins was aflatoxin B 1 . Natrolite treatment resulted in a 38% to 100% reduction in aflatoxin B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…While studying co-occurrence of patulin and aflatoxins in dried figs, Karaca and Nas (2006) reported (Senyuva et al 2008). Although the incidence of aflatoxin producing fungi is low in figs, different studies have shown that even a single individual fig with very high levels of aflatoxins can contaminate a large clean lot, as also observed in nuts (Doster et al 1996;Mohoney and Rodrigez 1996;Fooladi and Farahnaky 2003 (Table 3). In other words, 2007 was 1-2 C hotter year with 10-15% lower humidity than the previous four years.…”
Section: Resultsmentioning
confidence: 92%
“…While studying co-occurrence of patulin and aflatoxins in dried figs, Karaca and Nas (2006) reported (Senyuva et al 2008). Although the incidence of aflatoxin producing fungi is low in figs, different studies have shown that even a single individual fig with very high levels of aflatoxins can contaminate a large clean lot, as also observed in nuts (Doster et al 1996;Mohoney and Rodrigez 1996;Fooladi and Farahnaky 2003 (Table 3). In other words, 2007 was 1-2 C hotter year with 10-15% lower humidity than the previous four years.…”
Section: Resultsmentioning
confidence: 92%
“…A ation. At 45 t 45 t 45 t 45 t 45 Њ Њ Њ Њ ЊC, it was found to be r C, it was found to be r C, it was found to be r C, it was found to be r C, it was found to be rapid dur apid dur apid dur apid dur apid during the initial 5 h and slo ing the initial 5 h and slo ing the initial 5 h and slo ing the initial 5 h and slo ing the initial 5 (Moss 2002;Fooladi and Farahnaky 2003;Mishra and Das 2003). There are 4 principal types of aflatoxins, namely, B 1 , B 2 , G 1 , and G 2 .…”
Section: And and And And Amentioning
confidence: 97%
“…Increased production will require peanut traders in the region to seek external markets that impose strict safety standards. These stringent measures are mainly driven by the health implications of aflatoxin, which is both carcinogenic and immunosuppressive (Fooladi and Farahnaky, 2003), and the toxin's common presence in peanut and maize commodities (Council for Agricultural Sciences and Technology, 1989). For example, the European Union (EU) market has a tolerance level of 2 µg/kg for aflatoxin B1 and 4 µg/kg for total aflatoxin for peanut kernels imported into the EU (Sobolev, 2007).…”
Section: Introductionmentioning
confidence: 99%